UPGRADING THE STUDENTS’ ABILITY IN WRITING SKILL THROUGH IMPLEMENTATION OF DIRECTIVE FEEDBACK METHOD - Lisa Moulidia, Lisa Moulidia; Silvi Listia Dewi, Silvi Listia Dewi; Misnawati, Misnawati (Journal of English Education and Social Science, 2022)
The tittle of this thesis is Upgrading the Students’ Ability in Writing Skill through Implementation of Directive Feedback Method to the second years students of SMAN 1 Peudada (A collaborative Classroom Action Research). The researcher put two problems of this research question as follows: first, how can the Directive Feedback Method upgrade the second-year students of SMAN 1 Peudada in writing skill? Second, how do the students respond toward the implementation Directive Feedback Method in learning writing skill? The purpose of this research were: first, to know the Directive Feedback Method upgrade the second year students of SMAN 1 Peudada in writing skill. Second, to indicate the student’s response toward the implementation Directive Feedback Method in learning writing skill. This research was a collaborative classroom action research. The research subject was the second years students’ students of SMAN 1 Peudada. The sample of this research was 25 students. The data was collected through the field note, writing test, student’s observation checklist, teacher’s observation checklist and questionnaire. The data was analyzed through the descriptive qualitative research. After the researcher was done all the steps of action research (cycle I and cycle II) the students’ mean score increased from 61 in cycle I and became 76 in cycle II. Besides, from the observation checklist to the students’ activity, it was found that the percentage of the students’ participation during teaching learning process in writing class increased gradually. It was proved by the result of the observation checklist were taken at the beginning of cycle I, the percentage of the students’ participation was only 50 and became 62 in cycle II. And also, the list of questionnaires given to the students indicates that the student had positive respond toward the implementation of Directive Feedback Method in writing class. It was provided by overall mean score 31,52 that was categorized to the level of Agree.